2010
DOI: 10.1097/bcr.0b013e3181e4c8aa
|View full text |Cite
|
Sign up to set email alerts
|

Innovations in Caring for a Large Burn in the Iraq War Zone

Abstract: The authors report on a single case of a large, civilian burn cared for at a U.S. military hospital during Operation Iraqi Freedom. The management of the patient, using a large negative pressure wound therapy device and the Meek grafting technique, is reviewed. This is a case report. The patient survived his injury. In Iraq, most patients with this severity of injury succumb to the injury. By using two innovative techniques, the authors found that the patient was able to survive his injury and return to his ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…More recently, the use of micrograft transplantation with immediate 100-fold expansion for epidermal regeneration on both healthy and diabetic wounds in porcine models was reported [ 109 ]. In the same report, it was mentioned early clinical results confirmed the utility of this technique in a case report of a civilian patient with fifty-four percent total body surface area burn admitted to a U.S. Army military hospital in Iraq and successfully treated with the described micrografting technique [ 110 ].
Fig.
…”
Section: Reviewmentioning
confidence: 92%
“…More recently, the use of micrograft transplantation with immediate 100-fold expansion for epidermal regeneration on both healthy and diabetic wounds in porcine models was reported [ 109 ]. In the same report, it was mentioned early clinical results confirmed the utility of this technique in a case report of a civilian patient with fifty-four percent total body surface area burn admitted to a U.S. Army military hospital in Iraq and successfully treated with the described micrografting technique [ 110 ].
Fig.
…”
Section: Reviewmentioning
confidence: 92%
“…In a moist wound dressing environment, the dermal orientation of these micrografts did not matter which makes it an easily adaptable procedure. [ 5 16 25 ] In combination with minced grafts and skin substitute, a single-stage transfer has been described recently, which demonstrates the migration of keratinocytes and fibroblasts into the scaffold, a step towards obviating the necessity of cell cultures. [ 30 ]…”
Section: Dermal–epidermal Graftingmentioning
confidence: 99%
“…[ 3 ] Several reports of successful resurfacing of burns wounds above 60% are emerging using novel grafting techniques. [ 4 5 ] Hitherto available options of wound coverage in a resource-constrained donor site are traditional meshing techniques, multiple re-harvests from donor sites, use of amniotic membrane, allografts, xenografts and engineered skin sheets. [ 6 7 8 ] Skin expansion with a regular mesher is available with an expansion ratio of 1:1.5–1:9.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of the NPWT-treated burn with a less severe burn to the patient’s shoulder, which received standard therapy, revealed that NPWT yielded functionally and cosmetically superior results, with less hyperaemia and better skin quality. Another case report detailed the use of NPWT in a 54% TBSA full-thickness burn sustained by a civilian in the Iraqi war zone [92]. Although burns of this severity were typically fatal in Iraq, the patient survived his injury and was eventually discharged home.…”
Section: Introductionmentioning
confidence: 99%